IGF2BP3 promotes progression of gallbladder carcinoma by stabilizing KLK5 mRNA in N6-methyladenosine-dependent binding - Zhang, Junzhe; Yang, Kaini; Bu, Junfeng; Yan, Jiayan; Hu, Xiaoqiang; Liu, Ke; Gao, Si; Tang, Shuibin; Gao, Lili; Chen, Wei (Frontiers in Oncology, 2022)
Background Recent studies have reported that IGF2BP3 is linked to the pathogenesis of various malignancies. Since IGF2BP3 is associated with poor outcomes of gallbladder carcinoma (GBC), we aimed to explore the association between its N6-methyladenosine (m6A) RNA methylation and GBC progression. Methods Bioinformatic analysis of GSE136982, GSE104165, and RNA-seq was performed. In vitro and in vivo gain- and loss-of-function assays were done. qPCR, Western blotting, and IHC were conducted in cells or in collected clinical tissue samples. RNA immunoprecipitation, RNA stability measurement, methylated RNA immunoprecipitation, and dual-luciferase reporter assays were performed in this study. Results The expression of IGF2BP3 was higher in GBC tissues than in peritumoral tissues. Functions such as cell proliferation and migration, both in vitro and in vivo, were inhibited by downregulation of IGF2BP3. The analysis of RNA-seq indicated that KLK5 was a downstream target of IGF2BP3. The expression of KLK5 was measured in GBC cells and tumor samples. It was found to be positively correlated with IGF2BP3 level. Upon IGF2BP3 depletion, ectopic expression of KLK5 could rescue cell function in part. Mechanistically, we found that IGF2BP3 directly binds to KLK5 mRNA and regulates its stability in an m6A-dependent manner. As a result, inhibition of KLK5 decreased the expression of PAR2, and deregulated phospho-Akt. Using bioinformatic prediction combined with miRNA microarray analysis, we identified that let-7g-5p is an inhibitor of IGF2BP3, and let-7g-5p expression was negatively correlated with IGF2BP3. Overexpression of let-7g-5p affected the aggressive phenotype of GBC cells by deregulating IGF2BP3, and inhibiting the KLK5/PAR2/AKT axis. Conclusions Our data showed that IGF2BP3 is associated with the aggressive phenotype of GBC. Mechanistically, IGF2BP3 activated the PAR2/AKT axis by stabilizing KLK5 mRNA in an m6A-dependent manner. The loss of let-7g-5p enhanced the expression of IGF2BP3 and improved GBC progression. Thus, IGF2BP3 plays a crucial role in GBC, and the let-7g-5p/IGF2BP3/KLK5/PAR2 axis may be a therapeutic target for GBC.